Perceptions of graduate students on using wikis in a statistics class: A case study - Techanamurthy, Umawathy; Mohamad, Baharom; Mohd Hashim, Mohamad Hisyam; DeWitt, Dorothy; Alias, Norlidah (2014)
Wiki is an emerging technology being adopted in higher education. Among the uses of wikis in education are as a substitute for a course website, a communication medium between students and as an environment for writing collaborative assignments. However, there has been little research on the adoption of Wiki technology among Malaysian postgraduates. The participants of this research were pre-service academic staffs of Malaysian Polytechnics and Community Colleges taking their Masters in Technical and Vocational Education course. The purpose of this case study was to explore, understand and explain the various ways in which participants reflect on their very recent experiences in writing collaborative assignments in a Wiki. The Statistics in Technical Education Research for a Masters course for pre-service academic staffs was chosen as literature mentioned that statistics instruction should be similar to the way statistical practice is conducted collaboratively. For the purpose of this study, participants completed a wiki based group assignment. Data was collected from interviews, blog posts, Wiki log history and field notes. It was found that the possible educational advantages of wikis have not been fully utilized because of inadequate participation.This was because students faced problems when using the Wiki made them resort to discussing face-to-face first to divide their tasks. They resorted to the traditional way of completing group assignments but facilitated by technology. Hence, the potential educational benefits of wikis have not been fully exploited because of limited participation. However, several implications for implementing more effective wiki based learning were drawn from the interview data. On a positive note, students found wikis useful for sharing knowledge anytime as long as there was an Internet connection and they could critically assess change during peer editing. A conceptual model was developed based on the constructs from Technology Acceptance Model (Davis, 1987) and the Wiki Diffusion Model (Hester & Scott, 2008) to illustrate the findings of this study. This study is short-term and small-scale, so generalisable conclusions should not be made. This study was intended to be an initial pilot study to explore, understand and explain the various ways the participants used the Wiki rather than a defined program to use.